Les paysages périurbains de Roumanie, un développement non contrôlé marqué par ses héritages - Nicoleta Ticana (Projets de Paysage)
Peri-urban landscapes, these “third spaces” (M. Vanier, 2008), are in full developing in Europe. They appear under different forms, depending of countries, but also depending on local stakes. In Romania, and especially in Bucharest, these spaces are knowing different facets, heaving also a common point: growing urbanisation, hence rural and agricultural eroding space. In a country that has known communist system during many decades, where the urbanized space narrowing making part of the State policy, urban sprawl is on the agenda. The authorities are seeing that like a form of territorial development. Although periurban phenomenon knows dysfunctions, landscapes that result are very different of landscapes of twenty years ago. Occupied most often by residential zones, office spaces or commercial centres these spaces show a big attractivity.